ASOS IS A MEANINGFUL COMPONENT IN THE CURRENT UZBEKI LANGUAGE, ADDITIONAL OUTDATED OR INACTIVE UNITS (Multidisciplinary Journal of Science and Technology, 2024)
In this research work, we have analyzed a number of additional outdated or inactive units, even though the basis is considered a meaningful component in the current Uzbek language.